2005
DOI: 10.1590/s0004-282x2005000600005
|View full text |Cite
|
Sign up to set email alerts
|

Primary headaches in obese patients

Abstract: BACKGROUND AND OBJECTIVE: Obesity is a major public health problem worldwide. Little is known about the prevalence and impact of headache disorders in obese patients. The objective of this study was to assess the prevalence of primary headaches in obese patients and controls. METHOD: Seventy-four consecutive obese patients from the obesity surgery service were studied, and compared to controls with body mass index less than 25. RESULTS: Fifty-six patients (75%) had a headache diagnosis, 49 migraine (66%), 7 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 10 publications
5
42
0
Order By: Relevance
“…The literature data on this were conflicting [37,38]. The recent study suggested that the association between body mass index and migraine may be J-shaped [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The literature data on this were conflicting [37,38]. The recent study suggested that the association between body mass index and migraine may be J-shaped [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Peres et al [39] were the first assessing primary headache diagnosis in obese patients and migraine was the most common diagnosis, while chronic daily headache (chronic migraine and chronic TTH) was present in 12.2 %. In 2008, Keith et al [40] reported that a BMI of *20 was associated with the lowest likelihood of headache, while obese women had significantly increased risk for headache.…”
Section: Introductionmentioning
confidence: 99%
“…Horev et al (39) show that incidence of migraine headache among morbid obese individual was 48% higher as compared with non-obese control groups (40). Furthermore this observation was supported by Peres et al so that migraine headache was reported as 66% of obese patients in comparison with 18.5% of non-obese subjects (14). Moreover other studies have suggested that there is the association between migraine and obesity among men and in reproductive age women (39) and also in youngster age (37).…”
Section: The Association Between Morbid Obesity and Migraine Headachementioning
confidence: 85%
“…In addition, both obesity and migraine are important risk factors for chronic cardiovascular disease, myocardial infarction (7)(8)(9), ischemic stroke, and other inflammatory disease (10,11). Several studies showed that obesity is a risk factor for migraine development and frequency of headache in adults (12)(13)(14). The relationship between obesity and migraine would be important, since the increasing prevalence of obesity (15) may lead to an elevation in the prevalence, severity and frequency of migraine and may be a possible target for prevention.…”
Section: Introductionmentioning
confidence: 99%